Dracocephalum ruyschiana L. (pie Prensas (Antonopole)) - Lēmanis, Eduards (My University, 1883)
Nordischer Drachenkopf: Heidekieferwald bei Presna (Antonopol); Lichte Waldhange bei Nummern (1888.10.07.) /// Ruiša pūķgalve; Atradne: viršu priežu mežs pie Prensas (Antonopole); gaiša meža nogāze pie Numernes. /// Northern Dragon-head, deposit: heather pine forest near Prensa (Antonopole); a bright forest slope near Numerne. [Attēls no LU Muzeja kolekcijas Herbarium Latvicum (RIG II); (BOT1029_21)]
Keywords: Dracocephalum ruyschiana; ruiša pūķgalve; northern Dragon-head; Nordischer Drachenkopf; Antonopole; Numerne; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology